Influence of radiation and viscous dissipation on magnetohydrodynamic Jeffrey fluid over a stretching sheet with convective boundary conditions - Syazwani, Mohd Zokri; Nur Syamilah, Arifin; Muhammad Khairul Anuar, Mohamed; Mohd Zuki, Salleh; Abdul Rahman, Mohd Kasim; Nurul Farahain, Mohammad (UTM Press, 2017)
The present paper focuses on the influence of radiation and viscous dissipation on magnetohydrodynamic (MHD) flow and heat transfer of a Jeffrey fluid over a stretching sheet with convective boundary conditions (CBC). The governing equations are reduced to non-linear ordinary differential equations by using similarity transformation variables and then solved by using Runge-Kutta-Fehlberg method. The results generated from the numerical computations are presented in the form of tables and graphs for some values of Deborah number, ratio of relaxation to retardation times, Eckert number, radiation parameter and magnetic parameter. It is found that the distribution of fluid velocity is noticeably increased with an increment in Deborah number while the distribution of temperature shows the opposite trend.